Association of Herpesvirus and Periodontitis : a clinical and laboratorial case–control study - Picolo, Marta; Nobre, Miguel A de Araújo; Salvado, Francisco; Barroso, Helena (Thieme, 2023)
Objectives: A significant influence of the Herpesviridae family in the progression of periodontal disease has been suggested. The aim of this study was to investigate the potential association of four Herpesviruses (HSV-1, HSV-2, cytomegalovirus [CMV], and Epstein-Barr virus [EBV]) with periodontal disease using a qualitative test for evaluating the presence or absence of viral DNA in crevicular fluid samples of both healthy periodontal patients and periodontal compromised patients. Materials and methods: A case-control study was conducted in 100 participants at a university clinic. A qualitative test was used for evaluating the presence/absence of viral DNA in crevicular fluid samples of both healthy periodontal patients and periodontal compromised patients, and considering the periodontitis staging (stage II, stage III, and stage IV) and grading (grade A, grade B, and grade C). Statistical analysis: The distribution of the same exposure variables to the periodontitis staging and grading was compared using Chi-square, Fisher's exact, and Gamma tests depending on the variable characteristics. The significance level was set at 5%. The association of the variables: age, sex, diabetes, smoking, alcohol, and oral hygiene was also considered. Results: The prevalence of Herpesviridae family virus DNA was 6% for the periodontal healthy group and 60% for the periodontitis group (roughly 60% on periodontitis stages II, III, and IV, p <0.001; and twofold increase in moderate and rapid progression grades compared with the slow progression grade, p <0.001). HSV1 DNA was prevalent in all periodontitis stages and grades. HSV 2, EBV, and CMV DNA had increasing prevalence rates in more severe stages (stages III and IV, p <0.001); while considering periodontitis grade, HSV2 (p = 0.001), CMV (p = 0.019) and EBV (p <0.001) DNA were prevalent only in grades B and C, with EBV DNA registering a marked prevalence in grade C. Conclusion: A significant different distribution of Herpesviridae virus DNA per each stage of disease was registered.
Keywords: periodontitis; herpes simplex virus; Epstein-Barr virus; cytomegalovirus; epidemiology